Luminal endothelialization of small caliber silk tubular graft for vascular constructs engineering - Rizzi, Stefano; Mantero, Sara; Boschetti, Federica; Pesce, Maurizio (Frontiers in Cardiovascular Medicine, 2022)
The constantly increasing incidence of coronary artery disease worldwide makes necessary to set advanced therapies and tools such as tissue engineered vessel grafts (TEVGs) to surpass the autologous grafts (i.e. mammary and internal thoracic arteries, saphenous vein) currently employed in coronary artery and vascular surgery. To this aim, in vitro cellularization of artificial tubular scaffolds still holds a good potential to overcome the unresolved problem of vessel conduits availability and the issues resulting from thrombosis, intima hyperplasia and matrix remodeling, occurring in autologous grafts especially with small caliber (< 6mm). The employment of silk-based tubular scaffolds has been proposed as a promising approach to engineer small caliber cellularized vascular constructs. The advantage of the silk material is the excellent manufacturability for fiber deposition (i.e. electrospinning), the mechanical properties, the low immunogenicity and the extremely high in vivo biocompatibility. In the present work, we tested a new strategy to seed endothelial cells on the luminal surface of electrospun silk tubular scaffolds, based on low-speed rolling. We show that this strategy allows the formation of a nearly complete EC monolayer suitable for flow-dependent studies and vascular maturation, as a step toward derivation of complete vascular constructs for transplantation and disease modelling.